1981
DOI: 10.1136/vr.108.19.411
|View full text |Cite
|
Sign up to set email alerts
|

Acute fatal pneumonia in calves due to respiratory syncytial virus

Abstract: An acute pneumonia developed in 28 calves which had been housed together from one to two weeks of age. The clinical signs included pyrexia, tachypnoea, respiratory distress and coughing. Some of the calves died. The pneumonia was characterised by an alveolitis with multinucleated syncytia, alveolar epithelial hyperplasia and bronchiolitis. Interstitial emphysema was also present. Fifteen of 19 calves examined serologically had rising neutralising antibody titres to respiratory syncytial virus; in nine calves t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 0 publications
4
15
0
1
Order By: Relevance
“…It has been demonstrated that the human RSV virus is probably very commonly transferred by contact spread of large droplets between high-risk patients in hospitals (Hall and Douglas, 1981), while Mars et al (1999) recently demonstrated experimentally that BRSV can be transmitted by air between groups of calves in adjacent rooms. The pathological lesions seen after the combined aerosol and intratracheal exposure in the present study closely resembled the pathological lesions in acute BRSV-related pneumonia in the field (Bryson, 1993;Kimman et al, 1989;Pirie et al, 1981;Viuff et al, 1996); moreover, the infection progressed from the upper to the lower respiratory tract during 4-6 days (Viuff et al, accepted). Taken together, these findings indicate that the inoculation with aerosol for 10 min is probably quite close to the field exposure, where calves due to the close housing are continuously exposed to BRSV during an outbreak.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It has been demonstrated that the human RSV virus is probably very commonly transferred by contact spread of large droplets between high-risk patients in hospitals (Hall and Douglas, 1981), while Mars et al (1999) recently demonstrated experimentally that BRSV can be transmitted by air between groups of calves in adjacent rooms. The pathological lesions seen after the combined aerosol and intratracheal exposure in the present study closely resembled the pathological lesions in acute BRSV-related pneumonia in the field (Bryson, 1993;Kimman et al, 1989;Pirie et al, 1981;Viuff et al, 1996); moreover, the infection progressed from the upper to the lower respiratory tract during 4-6 days (Viuff et al, accepted). Taken together, these findings indicate that the inoculation with aerosol for 10 min is probably quite close to the field exposure, where calves due to the close housing are continuously exposed to BRSV during an outbreak.…”
Section: Discussionsupporting
confidence: 80%
“…This disease pattern, the clinical signs and the distribution and character of lung lesions in the BRSV-inoculated calves equalled descriptions of BRSV-related pneumonia in naturally infected calves (Belknap, 1993;Bryson, 1993;Kimman et al, 1989;Pirie et al, 1981;Viuff et al, 1996). The severity of elicited pneumonia did not correlate to the level of maternally derived neutralising antibodies at inoculation; and after the successful inoculation of colostrum-fed calves in experiment IV, we decided to focus on this type of calves to establish a more natural experimental model.…”
Section: Discussionsupporting
confidence: 70%
“…The pathological findings associated with experimental BRSV infection in lambs were similar to those reported in naturally and experimentally infected lambs (CUTLIP and LEHMKUHL, 1979;AL-DARRAJI et al, 1982a-c;TRIGO et al, 1984;LAPIN et al, 1993) and calves (PIRIE et al, 1981;VERHOEFF et al, 1984;BAKER and FREY, 1985;WEIKEL, 1990), although those natural infections were generally exacerbated by secondary infection with Pasteurella spp. (AL-DARRAJI et al, 1982a-c;TRIGO et al, 1984).…”
Section: Discussionsupporting
confidence: 71%
“…The main bronchial/ bronchiolar structures affected were the terminal bronchioles; the catharral bronchiolitis observed was associated with considerable neutrophil granulocyte infiltration. Similar changes have been described in naturally infected calves ( B R Y S O N~~ al., 1979;PIRIE et al, 1981;THOMAS et al, 1984;CASTLEMAN et al, 1985b) and in lambs (AL-DARRAJI et al, 1982b).…”
Section: Discussionmentioning
confidence: 98%
“…Macroscopically, the homogenous pathological alterations of the lungs are in contrast with the bimodal distribution of the lesions (cranio-ventral and dorso-caudal) usually reported in natural BRSV infections (Pirie et al, 1981;Kimman et al, 1989a, b;Ellis et al, 1996;Viuff et al, 1996;Baker et al, 1997). The peracute evolution of the disease leading to death often in 3 days could explain this discrepancy.…”
Section: Discussionmentioning
confidence: 95%